The clinicopathological significance of CDH1 in gastric cancer: a meta-analysis and systematic review - Zeng W; Zhu J; Shan L; Han Z; Aerxiding P; Quhai A; Zeng F; Wang Z; Li H (Dove Medical Press, 2015)
Wei Zeng,1,2,* Jinfeng Zhu,3,* Li Shan,2 Zhigang Han,2 Patiguli Aerxiding,2 Amina Quhai,2 Fanye Zeng,4 Ziwei Wang,5 Huiwu Li6 1College of Public Health, Xinjiang Medical University, Xinjiang, People’s Republic of China; 2First Department of Lung Cancer Chemotherapy, The Affiliated Cancer Hospital of Xinjiang Medical University, Xinjiang, People’s Republic of China; 3Department of Gastrointestinal Surgery, The Affiliated Cancer Hospital of Xinjiang Medical University, Xinjiang, People’s Republic of China; 4Department of Oncology, Traditional Chinese Medical Hospital Affiliated to Xinjiang Medical University, Xinjiang, People’s Republic of China; 5Department of Gastrointestinal Surgery, First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 6School of Basic Medicine, Xinjiang Medical University, Xinjiang, People’s Republic of China *These authors contributed equally to this work Background: CDH1 is a protein encoded by the CDH1 gene in humans. Loss of CDH1 function contributes to cancer progression by increasing proliferation, invasion, and/or metastasis. However, the association and clinicopathological significance between CDH1 hypermethylation and gastric cancer (GC) remains unclear. In this study, we systematically reviewed the studies of CDH1 hypermethylation and GC, and evaluated the association between CDH1 hypermethylation and GC using meta-analysis methods.Methods: A comprehensive search of the PubMed and Embase databases was performed for publications up to July 2014. Methodological quality of the studies was also evaluated. The data were extracted and assessed by two reviewers independently. Analyses of pooled data were performed. Odds ratios (ORs) were calculated and summarized.Results: A final analysis of 1,079 GC patients from 14 eligible studies was performed. CDH1 hypermethylation level in the cancer group was significantly higher compared to the normal gastric mucosa (OR =8.55, 95% confidence interval [CI]: 2.39–33.51, Z=5.47, P<0.00001). CDH1 hypermethylation was not significantly higher in GC than in adjacent gastric mucosa (OR =3.68, 95% CI: 0.96–14.18, Z=1.90, P=0.06). However, CDH1 hypermethylation was higher in adjacent gastric mucosa compared to that in normal gastric mucosa (OR =2.55, 95% CI: 1.22–5.32, Z=2.49, P<0.01). In addition, CDH1 hypermethylation was correlated with Helicobacter pylori (HP) status in GC. The pooled OR from six studies including 280 HP-positive GCs and 193 HP-negative GCs is 1.72 (95% CI: 1.13–2.61, Z=2.55, P=0.01).Conclusion: The results of this meta-analysis reveal that CDH1 hypermethylation levels in cancer and adjacent gastric mucosa are significantly higher compared to normal gastric mucosa. Thus, CDH1 hypermethylation is significantly correlated with GC risk. CDH1 hypermethylation is correlated with HP status, indicating that it plays a more important role in the pathogenesis of HP-positive GC and might be an interesting potential drug target for GC patients. Keywords: methylation, tumor suppressor gene, odds ratio